Trends in the development of digital literacy-based learning media for Indonesian language instruction in elementary schools from 2020 to 2025 - Ayub Prastiyo; Sri Wardani; Bambang Subali; Nuni Widiati (Direktorat Riset dan Pengabdian kepada Masyarakat UNY, 2026)
Over the past five years, advances in information technology have led to a significant increase in the use of digital literacy-based learning media in elementary schools. This trend has become more pronounced since the COVID-19 pandemic, which accelerated the shift from conventional to digital learning environments. This article aims to examine trends in the development of digital literacy-based learning media for Indonesian language instruction in elementary schools during the period 2020–2025. The study adopts a descriptive qualitative approach, employing a systematic literature review (SLR) combined with bibliometric analysis using VOSviewer software. The findings indicate that, since 2020, there has been a shift from the use of relatively simple digital media, such as PDF modules and instructional videos, toward more interactive formats, including Android-based applications, online learning platforms, and gamified media. Furthermore, the integration of digital literacy into Indonesian language instruction not only enhances students’ basic literacy skills but also promotes active engagement, collaboration, and creativity. However, several challenges persist, including unequal access to technology, limited teacher competence, and insufficient integration of local cultural contexts. This study concludes that future development of digital literacy-based learning media should move toward more innovative, inclusive, and sustainable approaches to better support the quality of Indonesian language learning in elementary schools.